WASIAT DALAM PANDANGAN HUKUM ISLAM DAN BW - Nur Aisyah (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2019)
AbstractThe inheritance must be shared with those who have the right to receive it, in the jurisprudence there is a discussion about the science of mawaris. According to the jurists, the science of mawaris is the knowledge of knowing people who have the right to receive heirlooms, people who cannot receive heirlooms, the levels received by each inheritance and how they are distributed. Testament is one of the forms of surrender or release of property in the Islamic Shari'ah. Testament has a very strong legal basis in the Shari'ah. Testament is also called testament is